POLITICAL PARTICIPATION OF WOMEN IN SELECTING LEGISLATIVE MEMBERS 2019-2024 PERIOD IN WEST SUMATERA PROVINCE - Hadi Prabowo; Ismail (GoAcademica Research dan Publishing, 2019)
The purpose of this study is to describe the factors causing the decline of women's involvement in the legislature in West Sumatra. The method used in this study is a qualitative method with descriptive type. The findings of this study indicate that the decline in representation of women in the West Sumatra DPRD from 7 people in the 2014-2019 period to 4 in the 2019-2024 period. This is due to (1) The perspective that considers the strong patriarchal paradigm in most Indonesian people, (2) Women have a multi-dual role to take care of domestic and public life, (3) People's mindset that tends to idolize brave men and bears to be elected, (4) Women do not choose women, meaning the low awareness of women to choose women legislative candidates, (5) Political organizations do not really have full commitment to empower women. Comprehensively, the role of women is very limited in policy making and decision making and leadership positions that are still held by men due to socio-cultural conditions which make it difficult for women to be fully involved in it.